Current state and development of the City park in Skopje - Jasminka Rizovska Atanasovska; Iskra Apostolovska; Nikolčo Velkovski; Vlatko Andonovski; Divna Penčić (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The City Park in Skopje was established in the early 20th century. There are not many historical data about its establishment. Only modest documentation could be found, for the period between the two world wars.